Developmental and hormonal regulation of ubiquitin-like with plant homeodomain and really interesting new gene finger domains 1 gene expression in ovarian granulosa and theca cells of cattle. (3rd July 2020) - Perego, Maria Chiara; Morrell, Breanne C; Zhang, Lingna; Schütz, Luis F; Spicer, Leon J
Abstract: Ubiquitin-like with plant homeodomain and really interesting new gene finger domains 1 (UHRF1 ) is a multi-domain nuclear protein that plays an important role in epigenetics and tumorigenesis, but its role in normal ovarian follicle development remains unknown. Thus, the present study evaluated if UHRF1 mRNA abundance in bovine follicular cells is developmentally and hormonally regulated, and if changes in UHRF1 are associated with changes in DNA methylation in follicular cells. Abundance of UHRF1 mRNA was greater in granulosa cells (GC ) and theca cells (TC ) from small (<6 mm) than large (≥8 mm) follicles and was greater in small-follicle GC than TC. In GC and TC, fibroblast growth factor 9 (FGF9 ) treatment increased ( P < 0.05) UHRF1 expression by 2-fold. Also, luteinizing hormone (LH ) and insulin-like growth factor 1 (IGF1 ) increased ( P < 0.05) UHRF1 expression in TC by 2-fold, and forskolin (an adenylate cyclase inducer) alone or combined with IGF1 increased ( P < 0.05) UHRF1 expression by 3-fold. An E2F transcription factor inhibitor (E2Fi ) decreased ( P < 0.05) UHRF1 expression by 44% in TC and by 99% in GC. Estradiol, progesterone, and dibutyryl-cAMP decreased ( P < 0.05) UHRF1 mRNA abundance in GC. Treatment of GC with follicle-stimulating hormone (FSH ) alone had no effect but when combined with IGF1 enhanced the UHRF1 mRNA abundance by 2.7-fold. Beauvericin (a mycotoxin) completely inhibited the FSH plus IGF1-induced UHRF1 expression in small-follicle GC. Treatments that increased UHRF1 mRNA (i.e., FGF9) in GC tended to decrease (by 63%; P < 0.10) global DNA methylation, and those that decreased UHRF1 mRNA (i.e., E2Fi) in GC tended to increase (by 2.4-fold; P < 0.10) global DNA methylation. Collectively, these results suggest that UHRF1 expression in both GC and TC is developmentally and hormonally regulated, and that UHRF1 may play a role in follicular growth and development as well as be involved in ovarian epigenetic processes.